Real time evaluation of monolateral clubfoot with sonoelastography. Preliminary results - Masala, Salvatore (CIC Edizioni Internazionali, 2012)
PURPOSE: to assess the real time elastosonography (RTE) as a primary diagnostic tool for the evaluation of mechanical properties of Achilles tendons in patients affected by not surgically treated monolateral clubfoot. MATERIALS AND METHOD: six patients were evaluated, four males and two females, mean age 1.2 ± 1.3 months, treated with Ponseti method, and afterward, they underwent RTE examination of the Achilles tendon in club-foot. A following ROI (region of interest) was positioned on the distal third of the tendon and the obtained data was examined retrospectively. RESULTS: in the examined cohort of patients, the mean value ROI 1/mean value ROI 2 ratio was 2.0 ± 0.18, with an increased red area in the RTE evaluation of the affected tendon, while in the contralateral foot the mean observed value was 2.50 ± 2.1. CONCLUSION: RTE is a feasible and simple technique, which allows the study of the mechanical properties of Achilles tendons in children with clubfoot.